Headteacher-teacher relationship and its effect on teacher's trust in Malaysian high performing schools. Issue 3 (9th April 2018) - Musah, Mohammed Borhandden; Abdul Rahman, Rozanne Emilia; Tahir, Lokman Mohd; Al-Hudawi, Shafeeq Hussain Vazhathodi; Daud, Khadijah
Abstract : Purpose: The purpose of this paper is to examine the relationship between headteachers and teachers and its effects on the role of trust in Malaysian high-performing schools through the dyadic relationship theoretical approach. Design/methodology/approach: Using a survey questionnaire, a total of 199 teachers from five high-performing schools were selected as respondents for data collection. Before proceeding with inferential statistical analysis, teachers were separated into the "in-group" and "out-group". Findings: The findings revealed that the teachers from both the groups perceived that their facets of trust are strongly associated with the type of relationship they have with their school leaders. The results also demonstrate that the quality of dyadic relationships between headteachers and teachers moderately influences teachers' trust. Practical implications: The findings suggest that the headteachers should always build good relationships with the teachers to gain teachers' trust for sustaining school effectiveness. The findings encourage the Ministry of Education, particularly the Teacher Recruitment Division, to require all teachers and headteachers to deepen their knowledge on leader-member exchange (LMX) role-development processes. Originality/value: The results are of great importance since limited empirical studies have examined LMX role-development processes with reference to teachers and headteachers in the context of Malaysian higher performing schools.